Saint-Hilaire’s Polygalaceae - Pastore, José Floriano Barêa (Phytotaxa, 2014)
This paper is a review of all Polygalaceae material on which the treatments of the family by Saint-Hilaire and Moquin-Tandon in 1828 and Saint-Hilaire in 1829 were based. It includes type designation for the names of all new taxa there proposed, except for Polygala paludosa var. ambigua. Some of the Saint-Hilaire and Moquin-Tandon’s names which were omitted in several Neotropical Polygalaceous treatments are here reviewed. Therefore, one of them, Polygala sellowiana, is here re-established as the correct name for the species better known as P. sabulosa. More detailed information is provided for Saint-Hilaire’s Polygalaceae collection.